The role of the teacher in identifying (non-Western) children in need for psychosocial care. (20th October 2021) - Eijgermans, DGM; Raat, H; Jansen, PW; Blok, E; Hillegers, MHJ; Jansen, W
Abstract: Background: The prevalence of mental health problems in Europe is higher among children with a non-Western than a Western background. Nevertheless, non-Western children use less psychosocial care. A possible explanation is the differences in parents' perceived need for care. Non-Western parents generally have a lower perceived need, which calls for other significant adults in the children's life to identify this need. This study investigates whether teachers could fulfil a role in identifying mental problems, especially in non-Western children, to improve the access to care. Methods: The study sample of 9-year-old children was retrieved from the Generation R Study (N = 3, 084), a population-based cohort of children born in Rotterdam, the Netherlands. Teacher- and mother-reported problems were measured at 6 years via questionnaires. Psychosocial care use was mother-reported at the research centre at 9 years (8.1% used care). Results: Our findings showed that, among children who used care, elevated problem levels at 6 years were reported for 10% by mothers and teachers, for 16% by mothers only and for 22% by teachers only. Hierarchical logistic regressions showed that having teacher-reported problems was associated with psychosocial care use (OR:3.06, p<.05), also after adjusting for mother-reported problems (OR:2.83, p<.05). Ethnic background did not moderate this association. Nonetheless, non-Western children did use significantly less care than Western children (OR:.58, p<.05), irrespective of their problem level. Conclusions: The association between teacher-reported problems and psychosocial care use suggests that teachers can play a role in identifying mental problems in children, in addition to parents. The role of the teacher might be particularly important for non-Western children in Western countries as their parents report on average a lower need for care, irrespective of the actual need. This calls for prevention strategies that focus on the teacher's unique position. Key messages: Teachers have an important role in the identification of mental health problems and access to psychosocial care for children. The signalling function of teachers is extra important for children with a non-Western migrant background as this group uses less care, irrespective of their problem level.